Impact of Improved Vegetable Technologies in Disadvantaged Districts of Uttar Pradesh - Neeraj Singh , Shubhadeep Roy , B. Singh & A.B. Rai, (Indian Journal of Extension Education, 2015)
Mirzapur and Sonbhadra, two disadvantaged districts in Uttar Pradesh, were the target area under the NAIP sub projectcomponent-3 during 2008-14. Both these districts are situated far south-east region of U.P. in the Vindhyan mountainrange. The baseline survey made during 2008-09 in the selected districts clearly indicated the lack of efficient agriculturaltechnology in the region and economic gap among the farmers. Intervention of various high yielding varieties along withimproved production and protection technologies in different vegetable crops not only increased the average productivityof the crops from 2.48 to 27.54 per cent but also enhanced the average annual income of the households. The increasedproductivity of vegetables has resulted in enhanced net return of ` 10298 to ` 34703 per hectare and the average annualincome of commercial vegetable growers was recorded as ` 59,695/- per household per year which is an improvement of50.7 per cent per household per year.